The NEAT1_2/miR-491 Axis Modulates Papillary Thyroid Cancer Invasion and Metastasis Through TGM2/NFκb/FN1 Signaling - Sun, Wei; Qin, Yuan; Wang, Zhihong; Dong, Wenwu; He, Liang; Zhang, Ting; Zhang, Hao (Frontiers in Oncology, 2021)
NEAT1 (nuclear paraspeckle assembly transcript 1) is an oncogenic long non-coding RNA (lncRNA) that facilitates tumorigenesis in multiple cancers. In papillary thyroid cancer (PTC), the molecular mechanism by which NEAT1 affects invasion and metastasis remains elusive. RNA sequencing was used to discover differentially expressed NEAT1_2 downstream genes. Protein and RNA expression analyses and immunohistochemistry detected the expression of NEAT1_2, Transglutaminase 2 (TGM2), and microRNA-491 (miR-491) among PTC and non-cancerous tissues. Transwell and wound healing assays, and a mouse model of lung metastasis were used for further functional analyses. Bioinformatics was performed to predict miRNAs binding to both NEAT1_2 and TGM2. Rescue experiments and dual-luciferase reporter assays were performed. In PTC tissues, NEAT1_2 expression was markedly increased and regulated TGM2 expression. TGM2 was overexpressed in PTC, correlating positively with exthyroidal extension and lymph node metastasis. TGM2 knockdown significantly inhibited invasion and metastasis. NEAT1_2 sponged miR-491, acting as a competing endogenous RNA to regulate TGM2 expression. Fibronectin 1 (FN1) was predicted as a TGM2 target. TGM2 could transcriptionally activate FN1 by promoting nuclear factor kappa B (NFκb) p65 nuclear translocation, ultimately promoting PTC invasion/metastasis. These findings identify that NEAT1_2 sponges miR-491 to regulate TGM2 expression. TGM2 activates FN1 via NFκb to promote PTC invasion and metastasis.